A review: the extraction of active compound from Cymbopogon sp. and its potential for medicinal applications - Shuhada, Abdul Muttalib; Raihana Z., Edros; Nor Azah, Mohd Ali; Kutty, Rajaletchumy V. (Universiti Malaysia Pahang, 2018)
Cymbopogon citratus and Cymbopogon nardus are plants categorized under the family of Poaceae that have been recognized with high demand in pharmaceutical industry for its wide range of pharmacological activities. The potential bioactive compounds can be obtained either through traditional or conventional methods. The plant extracts are commonly used in numbers of products for culinary, pesticides and cosmetic purposes for its flavours and fragrances. Besides, bioactive compounds extracted from both species possess good biological activities that can be applied in the pharmaceutical field.